Airborne radar imaging of subaqueous channel evolution in Wax Lake Delta, Louisiana, USA - John B. Shaw; Francois Ayoub; Cathleen E. Jones; Michael P. Lamb; Benjamin Holt; R. Wayne Wagner; Thomas S. Coffey; J. Austin Chadwick; David Mohrig (Geophysical Research Letters)
Abstract Shallow coastal regions are among the fastest evolving landscapes but are notoriously difficult to measure with high spatiotemporal resolution. Using Uninhabited Aerial Vehicle Synthetic Aperture Radar (UAVSAR) data, we demonstrate that high signal‐to‐noise L band synthetic aperture radar (SAR) can reveal subaqueous channel networks at the distal ends of river deltas. Using 27 UAVSAR images collected between 2009 and 2015 from the Wax Lake Delta in coastal Louisiana, USA, we show that under normal tidal conditions, planform geometry of the distributary channel network is frequently resolved in the UAVSAR images, including ~700 m of seaward network extension over 5 years for one channel. UAVSAR also reveals regions of subaerial and subaqueous vegetation, streaklines of biogenic surfactants, and what appear to be small distributary channels aliased by the survey grid, all illustrating the value of fine resolution, low noise, L band SAR for mapping the nearshore subaqueous delta channel network.